MEMECAH DORMANSI RIMPANG TEMULAWAK (Curcuma xanthorrhiza ROXB) MENGGUNAKAN LARUTAN ATONIK DAN STIMULASI PERAKARAN DENGAN APLIKASI AUKSIN - Djamhari, Sudaryanto (Badan Pengkajian dan Penerapan Teknologi, 2010)
Temulawak is a plant propagated vegetatively with rhizomes. Its rhizome undergoes a dormancy phase in dry season and this phase will break up in wet season. The objective of this study is to know the dormancy breaking by soaking the temulawak rhizome in stimulating biology liquid (0, 2, 4, 6 ml/l) and commercial auxin liquid (0, 10, 20, mg/l). The result showed that both liquid could stimulate the dormancy breaking. However those treatments were not different with control (biology liquid 0 g/l and commercial auxin 0 mg/l ). The number of shooting rhizomes, total shoots, rooted rhizomes and total roots in all treatment were not significantly different from the control.